2017
DOI: 10.1186/s12944-017-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene polymorphism modifies fasting total cholesterol concentrations in response to replacement of dietary saturated with monounsaturated fatty acids in adults at moderate cardiovascular disease risk

Abstract: BackgroundConsumption of ≤10% total energy from fat as saturated fatty acids (SFA) is recommended for cardiovascular disease risk reduction in the UK; however there is no clear guidance on the optimum replacement nutrient. Lipid-associated single-nucleotide polymorphisms (SNPs) have been shown to modify the lipid responses to dietary fat interventions. Hence, we performed a retrospective analysis in 120 participants from the Dietary Intervention and VAScular function (DIVAS) study to investigate whether lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Apolipoprotein E is one of the major proteins involved in the transport of cholesterol and TG within the circulation [ 53 ]. A 2017 retrospective analysis of 120 participants enrolled in the DIVAS study, a parallel design based on a food-exchange model of SFA, monounsaturated fatty acid (MUFA), and polyunsaturated fatty acid (PUFA) intakes in free-living individuals for 16 wk, reported that only APOE rs1064725-TT homozygotes, but not G allele carriers, showed a reduction in serum TC concentrations after the MUFA diet (−0.71 ± 1.88 mmol/L) compared to the SFA (0.34 ± 0.55 mmol/L) or n-6 PUFA diets (−0.08 ± 0.73 mmol/L) [ 23 ]. A German diabetes study evaluated the interaction between dietary patterns, using FFQ data, and APOE polymorphisms in 348 diabetic patients, where among carriers of the APOE ε2 isoform (E2/E2, E2/E3; rs429258: TT, rs7412: TT/CT), lower versus higher consumption frequencies of butter, cream cake, French fries, or alcoholic beverages were independently associated with a 40% reduction in serum LDL-C concentrations [ 24 ].…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…Apolipoprotein E is one of the major proteins involved in the transport of cholesterol and TG within the circulation [ 53 ]. A 2017 retrospective analysis of 120 participants enrolled in the DIVAS study, a parallel design based on a food-exchange model of SFA, monounsaturated fatty acid (MUFA), and polyunsaturated fatty acid (PUFA) intakes in free-living individuals for 16 wk, reported that only APOE rs1064725-TT homozygotes, but not G allele carriers, showed a reduction in serum TC concentrations after the MUFA diet (−0.71 ± 1.88 mmol/L) compared to the SFA (0.34 ± 0.55 mmol/L) or n-6 PUFA diets (−0.08 ± 0.73 mmol/L) [ 23 ]. A German diabetes study evaluated the interaction between dietary patterns, using FFQ data, and APOE polymorphisms in 348 diabetic patients, where among carriers of the APOE ε2 isoform (E2/E2, E2/E3; rs429258: TT, rs7412: TT/CT), lower versus higher consumption frequencies of butter, cream cake, French fries, or alcoholic beverages were independently associated with a 40% reduction in serum LDL-C concentrations [ 24 ].…”
Section: Studies Investigating the Effect Of Snps Taken Individualmentioning
confidence: 99%
“…For example, Shatwan et al . (18) examined the impact of diets high in SFA, MUFA or n -6 PUFA over 16 weeks. Stratifying for ApoE SNP (rs1064725), they reported that only TT homozygotes showed a significant reduction in total cholesterol after the MUFA diet compared to the SFA or n -6 PUFA diets (18) .…”
Section: Genotypic Variation Influencing Response To Nutrition Intervmentioning
confidence: 99%
“…(18) examined the impact of diets high in SFA, MUFA or n -6 PUFA over 16 weeks. Stratifying for ApoE SNP (rs1064725), they reported that only TT homozygotes showed a significant reduction in total cholesterol after the MUFA diet compared to the SFA or n -6 PUFA diets (18) . However, one must remember that whilst a study may be examining impact of genotype, that this may not be the only factor influencing response, for example, Caslake et al .…”
Section: Genotypic Variation Influencing Response To Nutrition Intervmentioning
confidence: 99%
“…14,15 From the nutritional viewpoint, various studies have confirmed that a diet with a low amount of saturated fatty acids and high content of MUFA can effectively reduce the risk of coronary heart disease amending blood lipid levels and blood pressure ameliorating metabolic syndrome and insulin sensitivity. [18][19][20][21]…”
Section: Lipids and Fatty Acidsmentioning
confidence: 99%